Pathogenesis of Immune-Mediated Glomerulonephritis - Nur Samsu (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Most forms of glomerulonephritis (GN) are characterized by a pathogenic immune response, which is mediated by the action of various immune system elements, both innate and adaptive. What is clear is that the immunopathogenesis of GN is very broad and complex. Deposits of immune complexes in the glomeruli activate complement and glomerular injury due to the involvement of circulating inflammatory cells and glomerular intrinsic cells, ultimately resulting in a wide variety of clinical manifestations, which depend in part on the location and immunopathology of the patient, including genetic and environmental factors, from asymptomatic to rapidly progressive GN. Most of the treatment strategies for GN are non-specific, consisting of corticosteroids and cytotoxic agents. Thus, an advanced understanding of GN immunopathogenesis may offer many opportunities for future therapeutic interventions on an individual basis. To further facilitate understanding of the pathogenesis of GN, the author also includes a graphical abstract.